Early identification of golimumab-treated patients with higher likelihood of long-term retention - García-Dorta, Alicia; González-Dávila, Enrique; Sánchez-Jareño, Marta; Cea-Calvo, Luis; Pombo-Suárez, Manuel; Sánchez-Alonso, Fernando; Castrejón, Isabel; Díaz-González, Federico (Frontiers in Immunology, 2024)
Background: The early identification of patients’ profiles most likely to respond to and maintain long-term therapy with a biological drug can have clinical and cost-effectiveness implications. Objectives: To evaluate the utility of an innovative approach for early identification of patient profiles associated with long-term persistence of golimumab, a tumour necrosis factor inhibitor, in patients with rheumatoid arthritis (RA), psoriatic arthritis (PsA), and axial spondyloarthritis (SpA) under real-world conditions. Design: Retrospective non-interventional database analysis. Methods: Kaplan-Meier curves of golimumab retention over 8 years from the BIOBADASER registry, overall and by indication, were analysed using a novel approach (a two-phase decay model) to identify the point at which the golimumab retention curve shifted from rapid (indicating high golimumab discontinuation rate) to slow decay (low discontinuation rate). Factors associated with golimumab retention at these time points were identified using Cox regression, and retention rates for different patient profiles were calculated. Results: 885 patients were included. The golimumab retention curve shifted from rapid to slow decay at month 10 for the overall population (retention rate: 73.4%), at month 24 for RA patients (retention: 45.0%), and at month 8 for SpA, including axial SpA and PsA (81.6%). Factors associated with golimumab discontinuation at these early points were, overall, similar to those previously identified at year 8 (RA diagnosis, golimumab as second- or third-line of biological therapy, disease activity over the median and treatment with corticosteroids at golimumab initiation, advanced age [in RA], and female gender [in SpA]). Conclusions: With this novel approach, the factors associated with long-term retention were identified in the initial period of rapid discontinuation of golimumab.